Maternal secure base support and preschoolers' secure base behavior in natural environments - Kaloustian, Garene (2007)
Bowlby and Ainsworth's theory of attachment poses that concurrent caregiving behavior is a key factor in influencing and maintaining a child's organization of secure-base behavior, and ultimately, security throughout childhood. Empirical demonstrations of the relation between the constructs after infancy are relatively scant and research is needed to examine the relation between the variables across a wide range of contexts, over longer observational periods, and in developmentally appropriate ways. Two studies of preschoolers and their mothers were conducted in naturalistic settings. Fifty child-mother middle-class dyads, predominantly Caucasian, participated in Study 1 and 40 in Study 2. The mean age for children was 52 months (Study 1) and 36 months (Study 2). In Study 1, a home and a playground visits were conducted. In Study 2, two home and a playground visits were conducted. Observers used the Maternal Behavior for Preschoolers Q-Set to provide age-relevant descriptions of maternal behavior, and the Attachment Q-Set to provide descriptions of child behavior. Overall, findings indicated that maternal secure base support was significantly related to the organization of child secure base behavior (r = .31 and .49 for Study 1 and Study 2, respectively). Results are discussed in terms of the importance of specifying caregiving domains and contexts of assessments, and their implications for attachment theory.